Microscopic composition of ion-ion interaction potentials - Umar, A. S.; Oberacker, V. E.; Maruhn, J. A.; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2012)
We present a new method to calculate the total ion-ion interaction potential in terms of building blocks, which we refer to as "single- particle interaction potentials." This allows also the composition of the separate contributions of neutrons and protons to the interaction potentials. The method is applied to nuclear collisions via the use of time-dependent Hartree-Fock theory. © 2012 American Physical Society.
CRIS-Team Scopus Importer:2023-07-24